SnoN and Ski protooncoproteins are rapidly degraded in response to transforming growth factor β signaling - Sun, Yin (The National Academy of Sciences, 1999)
Transforming growth factor β (TGF-β) regulates a variety of physiologic processes, including growth inhibition, differentiation, and induction of apoptosis. Some TGF-β-initiated signals are conveyed through Smad3; TGF-β binding to its receptors induces phosphorylation of Smad3, which then migrates to the nucleus where it functions as a transcription factor. We describe here the association of Smad3 with the nuclear protooncogene protein SnoN. Overexpression of SnoN represses transcriptional activation by Smad3. Activation of TGF-β signaling leads to rapid degradation of SnoN and, to a lesser extent, of the related Ski protein, and this degradation is likely mediated by cellular proteasomes. These results demonstrate the existence of a cascade of the TGF-β signaling pathway, which, upon TGF-β stimulation, leads to the destruction of protooncoproteins that antagonize the activation of the TGF-β signaling.